Spectroscopic Characteristics and Color Origin of Red Tourmaline from Brazil - Li, Ming (Journal of Spectroscopy, 2022)
In the present paper, I report on the spectroscopic study for tourmaline color origin, performed red samples from Minas Geras State, Brazil, by gemological routine testing, X-ray diffraction, Fourier transform infrared spectroscopy, ultraviolet-visible spectroscopy, and X-ray photoelectron spectroscopy. The main goal was the analysis of the optical absorption spectra and the chemical states of transition metal cations in order to better understand the effect of transition metal cations on color of tourmaline. The results showed that the red color was confirmed by the symmetric broad absorption at 527 nm and the narrow absorption at 400 and 450 nm, and the above three absorption bands were caused by the d-d electron transition of Mn3+, which occupied the Y site in the crystal structure and coordinated with F to form bonds. In addition, in principle, the chemical states of the chromogenic ions in tourmaline and their influence on coloration were confirmed, which would be beneficial to assessing the color change and identifying the origin of tourmaline.